Monochromatic X-Ray Imagers of the Sun Based on the Bragg Crystal Optics - Reva, Anton A.; Kuzin, Sergey V.; Kirichenko, Alexey S.; Ulyanov, Artem S.; Loboda, Ivan P.; Bogachev, Sergey A. (Frontiers in Astronomy and Space Sciences, 2021)
Investigations of solar activity require information about plasma in a wide range of temperatures. Generally, researchers require observations from telescopes producing monochromatic images of coronal plasma with cool, warm, and hot temperatures. Until now, monochromatic telescopic imaging has been made only in the Mg XII 8.42 A line with the Mg XII spectroheliograph on board CORONAS-I, CORONAS-F, and CORONAS-PHOTON satellites. The Mg XII spectroheliograph used Bragg crystal optics. Its design is based on two main principles: 1) to select the working wavelength and the crystal in such a way that reflection occurs at small incident angles; 2) to use the aperture of the mirror as a spectral filter. We believe that these design principles can be applied to other spectral lines. In this article, we will review the design of the Mg XII spectroheliograph and present our thoughts on how to apply these principles to the Si XIV 6.18 A and Si XIII 6.65 A lines. A combination of the monochromatic Mg XII 8.42 A, Si XIV 6.18 A, and Si XIII 6.65 A images will help us to study the dynamics of the hot plasma in the solar corona.